L'islam des musées: La mise en scène de l'islam dans les politiques culturelles françaises - Guidi, Diletta (Culturel, 2022)
Paris, Kuala Lumpur, New York, Doha, Berlin, Honolulu, La Chaux-de-Fonds: each of these cities hosts a museum of Islamic art, and many more can be added to this list. Since the 2000s, and in particular after the 9/11 attacks, more and more cultural institutions have invested in this sector. In this context of international museums’ “Islamania”, for the very first time this book looks at the case of France, through the examples of the Louvre Museum and the Institut du monde arabe. By analyzing the staging of Islam, from the Colonial Exhibitions of the 19th century to the present day, this work shows how such staging is the reflection of public policies regarding the Muslim religion and how the French State uses it to manage Islamic otherness. More broadly, the museums’ treatment of Islam makes it possible to reflect on the regulation of religion and consequently on secularism. It also illustrates the political and social tensions caused by the presence of Islam in France and, by extension, the place of the Other in now multicultural and globalized Western societies. “Islam of museums” thus goes beyond mere observation of the history of an artistic genre, it provides a new perspective on our cultural, political, social, and religious history